Organizational and marketing prerequisites for the effective conduct of student competitions: the case of boxing - Burtsev, V.A.; Rukavishnikov, D.A.; Schneider, M.G. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify ways to improve the organization of student sports events from the perspective of sports marketing. Methods and structure of the study. We analyzed the experience of organizing and conducting a Boxing show according to the rules of the World Series of Boxing (WSB), dedicated to World AIDS Day, titled "Live Boxing," at the Volga State University of Physical Culture, Sports, and Tourism. We also conducted surveys to identify factors influencing attendance at student sports events and to assess the success of the "Live Boxing" sports event. The first survey involved 120 respondents, and the second involved 186 people. Results and conclusions. The organization and conduct of the WSB Boxing show, dedicated to World AIDS Day and titled "Live Boxing," involved four stages: Stage 1: Development of the project proposal (initial situation, project goal, project objectives, risks, budget). Stage 2: Marketing of the WSB Boxing show (personal marketing, place marketing, organization marketing, idea marketing). Stage 3: Development of the Boxing show script. Stage 4: Conducting the Boxing show. The ways to improve marketing activities for attracting fans and spectators to student sports events include: show organization; comfort and safety; unconventional advertising; and opportune timing.